Mastering spice : recipes and techniques to transform your everyday cooking - Sercarz, Lior Lev; Ko, Genevieve (Clarkson Potter/Publishers, 2019)
Spices are the fastest, easiest way to transform a dish from good to spectacular. In his new book, Lior Lev Sercarz, the country's most sought-after spice expert, shows you how to master flavor in 250 inspiring recipes, each counting on spices to elevate this collection of everyday and new favorites. Spices are the magic ingredient in Lior Lev Sercarz's newest book, Mastering Flavor, and all it takes is a pinch to bring your meatballs, roast chicken, or brownies to the next level. Owner of the spice shop, La Bo te in New York City, and a professionally trained chef who has cooked at some of the world's most renown restaurants, Lior's simple and straightforward approach showcases how spices and spice blends can take a recipe for chicken soup, meatballs, or brownies into a whole new and exciting direction. Every section begins with a master recipe and technique--then Lior teaches readers how to change the spices or some of the ingredients to get a profoundly different dish than what you began with. By mastering the techniques and playing with the variations, you'll learn how to use spices to become a more creative and intuitive cook, and how spices can endlessly heighten your eating experience.